Association between social relationship of mentors and depressive symptoms in first-time mothers during the transition from pregnancy to 6-months postpartum - Malgorzata Gasperowicz; Karen M. Benzies (Maternal Health, Neonatology and Perinatology, 2024)
Abstract Background First-time motherhood is characterized by high psychosocial distress, which untreated, has serious consequences. Informal social support provided by specially trained mentors may be protective against postpartum depressive symptoms but may vary by women’s social relationship with the mentor. The objective of this study was to evaluate the association of types of mentors on women’s depressive symptoms between late pregnancy to 6-months postpartum and the characteristics of women associated with mentor type. Methods This study was a secondary analysis of data from a community sample of 312 primiparous women from a single-group, longitudinal intervention study of Welcome to Parenthood. Welcome to Parenthood provided education and mentorship for women during the transition from pregnancy to postpartum. Women completed the Edinburgh Postnatal Depression Scale (EPDS) in late pregnancy, and 2- and 6-months postpartum. Results Women who recently relocated were less likely to be mentored by their mothers and more likely to be mentored by friends or volunteers. Women who were mentored by their mothers or sisters scored the lowest on the EPDS; those mentored by their mothers-in-law scored the highest. Women who were mentored by other family, friends, or volunteers scored between the two extremes. EPDS scores of women mentored by each type of mentor decreased from pregnancy to 6-months postpartum; only for mother-, sister-, and volunteer-mentored groups was this decrease significant. Conclusions During transition to parenthood, support provided by mothers or sisters is best for women’s mental health but may not always be available to women who have recently relocated. In such situations, specially trained community volunteers may be the second-best option.